If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -11 = 1 Reorder the terms: -11 + y = 1 Solving -11 + y = 1 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + y = 1 + 11 Combine like terms: -11 + 11 = 0 0 + y = 1 + 11 y = 1 + 11 Combine like terms: 1 + 11 = 12 y = 12 Simplifying y = 12
| -108=-3+7(7b-8) | | 4+y=15 | | 12x-5-8x+5=x-8x+5 | | 4x+10+10=180 | | 8y-(-5y-15)=13 | | y-15=-10 | | x^2+11x=4x+49 | | y+7y=40 | | 8h+3=75 | | -5n(4-3n)=10(n-2) | | 2x+2(4x)+38=180 | | 7-2n=8n(4n) | | 0.875p=-3.75 | | 7y-3x+8=0 | | 0.06666666666666666666666666666667-0.1666666666666667v=0.5333333333333333 | | x^2+7x=26 | | 10m-20=80 | | 5n+10= | | 14-y=0 | | 4x-3x=-6+8 | | 1+y=16 | | 3h+2=5h-15 | | -7j+-4j= | | y-0.4y= | | 5a/6-4=1 | | 4x+-6x+2x= | | y-0.4= | | 13=6j-7-1j | | 6x-2(4x)+38=180 | | 3(5x-2)+50=8x+2 | | .66(x)=.33 | | -2x+7x+2+4=10x+14 |